2012
DOI: 10.1007/s12185-012-1220-9
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence for an inherited genetic basis of childhood acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is the most common cancer in children, and efforts to understand its etiology has followed a paradigm that common genetic variation in the presence of modifiable environmental factors contribute to disease risk. To date, there are numerous reports of candidate gene association studies suggesting an involvement of genetic loci in childhood ALL risk, but the general lack of consistency in results has underscored the need for careful interpretation and confirmation in additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 106 publications
(159 reference statements)
0
14
0
Order By: Relevance
“…Acute lymhoblastic leukemias (ALLs) are neoplasms of lymphoid precursors and are common among childhood malignancies [55]. With the advent of high-resolution genome-wide profiling approaches, a variety of genetic alterations, deletions and mutations have been newly identified on the ALL genomes that cooperate with previously characterized chromosomal alterations [56-58].…”
Section: A New High-risk Model Of B-all Supported By Ikaros Mutationsmentioning
confidence: 99%
“…Acute lymhoblastic leukemias (ALLs) are neoplasms of lymphoid precursors and are common among childhood malignancies [55]. With the advent of high-resolution genome-wide profiling approaches, a variety of genetic alterations, deletions and mutations have been newly identified on the ALL genomes that cooperate with previously characterized chromosomal alterations [56-58].…”
Section: A New High-risk Model Of B-all Supported By Ikaros Mutationsmentioning
confidence: 99%
“…As reviewed previously [55], the two approaches should be viewed as complementary strategies for identification of disease associated loci as they both have their respective strengths and weaknesses depending on the study being conducted. A review of the literature identified six xMHC childhood ALL candidate gene studies of non-classical HLA loci, and statistically significant associations have been reported for SNPs of the HFE , HSPA1B and BAT3 genes [56,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Using technological approaches available at the time, study investigators most often looked at SNPs within single genes that were thought to be involved in the process of leukemia development and progression. When reviewing the hundreds of published studies available, the majority of these candidate genes associated with the biology of ALL can be divided into the following 5 main categories: (1) folate metabolism/transport, (2) xenobiotic metabolism/transport, (3) immune function, (4) DNA repair, and (5) cell cycle 9 10. Many of these studies have mixed and even conflicting results, demonstrating the difficulty in identifying risk genes for cancer.…”
Section: Candidate Gene Approachesmentioning
confidence: 99%